Analysis of the Aptitude Test as Indicator of the Timely Graduation of the Students of the College of Architecture and Fine Arts – Polytechnic University of the Philippines - et. al., Jocelyn A. RIVERA LUTAP (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Gunnar Myrdal’s statement in 1971, “It becomes expensive if we cannot afford it,” has consistently proved to be truer more than ever. As PUP faces the challenge of maintaining and improving the quality of education to as many deserving but financially challenged students with very scarce resources there is a need to establish a protocol to assess the students other than the PUPCET examination and their high school ratings in Math, Science and English. The assessment is necessary in order to complement and supplement the required skills they need to finish the BS Architecture and BS Interior Design programs within the prescribed period to ensure the sustainability of the programs in the College of Architecture and Fine Arts. The primary objective of the admission officer is to focus on admitting students who possess the potential to succeed academically in the institution. It benefits neither the institution nor the students to admit an applicant that is not likely to persist. (Evans, 2011) The aptitude examination is designed to be able to quantify the result of the exam and provides measures on the aspect of ability needed in the program. The aptitude exam will demonstrate potential talent through sense of scale, a sense of space, accuracy of observation, and attention to details